Silagem de grão de sorgo reidratado com água ou soro de leite - Faustino, Thailson Fernando (2016)
The objective of this research was to evaluate the nutritional quality of sorghum silage processed and rehydrated with water or whey. The experimental design was a completely randomized 4x2x2 factorial design, with rehydration of the grain in four moisture contents (25, 30, 35 and 40%), rehydration with water or whey and, with or without the addition of bacterial inoculant, totaling 16 treatments with four replicates each. The sorghum grains were ground, rehydrated and conditioned in experimental PVC silos with capacity of 4.5 kg for 90 days, to evaluate the aerobic stability as well as the microbiological and chemical-bromatological characteristics of the silage. The results were submitted to analysis of variance of the statistical program SAS (9.2), and the humidity levels were evaluated by linear and quadratic orthogonal contrasts and, the vehicle of rehydration and inoculant were compared by F test. The use of water compared to the whey in the rehydration decreased the losses by gases, effluents and dry matter of the silages. The increase of moisture in the silages promoted a lower development of fungi and yeasts. The inoculated silages showed higher dry matter contents in relation to the silages without inoculant. The crude protein (CP) concentration in the grain silage of rehydrated sorghum was not altered as a function of the treatments. The addition of inoculant decreases the concentration of acid detergent fiber (ADF), the lowest values being in the silage with 40% moisture with water. Silage rehydrated with whey had higher values of mineral matter, compared to silages rehydrated with water. The use of whey in the rehydration of sorghum grains for silage is a good strategy to avoid its disposal in the environment, and its addition is recommended to the point where the sorghum grain reaches 30% moisture. In addition, it is recommended to use the bacterial inoculant, as it ensures less fermentative loss in the process with greater aerobic stability of the silages.